Prevalence and factors associated with intestinal parasitic infections among preschool-aged children in Ethiopia: A systematic review and meta-analysis - Abayeneh Girma; Amere Genet (Parasite Epidemiology and Control, 2024)
Intestinal parasitic infections (IPIs) pose a serious public health threat across the globe, particularly in children residing in poor and most deprived communities like Ethiopia. Many published articles were available separately, and a detailed nationwide review was essential to combine all the results to draw a conclusion and avoid any informational conflicts, ambiguities, or misunderstandings. Therefore, this systematic review and meta-analysis aimed to provide pooled estimates for the individually available data on IPIs and its determinant factors among preschool-aged children (PSAC) in Ethiopia. Published and unpublished articles from various electronic databases were accessed using MeSH terms and keywords. I2 and sensitivity analysis tests were used to assess potential sources of heterogeneity across studies. Funnel plot, Begg's, and Egger's regression tests were used to check publication bias. A random-effects model with a 95% confidence interval (CI) was used to calculate the pooled estimate of IPI. In this meta-analysis, a total of 14,994 PSAC were included in the 32 eligible studies. The pooled national prevalence of IPIs among PSAC was 32.52% (95% CI: 26.24, 38.80). Of these, single and mixed infections contribute 31.08% and 1.44%, respectively. According to the subgroup analysis, the highest prevalence was observed in simple random studies (39.61%; 95% CI: 29.19, 50.03), the Tigray region (58.00%; 95% CI: 54.10, 61.90), studies conducted in >384 (39.47%; 95% CI: 27.73, 51.20) sample sizes, cross-sectional studies (32.76%), community-based studies (42.33%; 95% CI: 31.93, 52.74), and from 2005 to 2016 (34.53%; 95% CI: 20.13, 48.92) study periods. Intestinal parasites were significantly associated with eating raw fruits and vegetables (aOR = 3.21; 95%CI: 1.11–5.31). The high prevalence of STHs observed in this systematic review and meta-analysis underscores the need for appropriate control and prevention strategies suitable for PSAC in Ethiopia.